Respuesta :

ROTRUY

Answer:

Step-by-step explanation:

So, you are given an equation with two variables. Normally, you'd need two equations to solve this, but in this case we are given the value for one of the variables two times, so this is quite simple once you understand it.

Our first solution set is given as (9,?). This means we must find what y is equal to. To do this, we simply fill in the given x value (9) and equate to y as follows:

2x + 3y = 12

⇒ 2 · 9 + 3y = 12

⇒ 3y = 12 - 2 · 9 = -6

⇒ y = -6/3 = -2

Thus, the first solution is (9,-2). If we check to see if this is correct we find that 2·9 + 3·(-2) = 18 - 6 = 12 and indeed it is correct. For the next one, we are given the value for y and can thus equate to x:

2x + 3y = 12

⇒ 2x + 3 · 4 = 12

⇒ 2x = 12 - 3 · 4 = 0

⇒ x = 0/2 = 0

And the second solution set is then (0,4).
Check to be sure: 2·0 + 3·4 = 0 + 12 = 12 , yes indeed it is.